MAJORITY SHAREHOLDER : LARGE SHAREHOLDER, FAMILY OWNERSHIP, INSTITUTION OWNERSHIP AND ITS IMPACT ON FIRM PERFORMANCE - Roossiana, Artalia Indah; Bustaman, Yosman (Academic Research Centre Services, 2015)
We investigate the impact of majority shareholder that categories as large shareholder, family ownership and institution ownership on the firm performance measured bu accounting performance ROA and market performance namely Tobin Q. This research concentrate on Consumer Goods Sector Companies listed on the Indonesia Stock Exchange (IDX) covering from year 2011 to year 2014. We use unbalanced panel data analysis. After controlling with firm specific variables; such as size of company, age, leverage, growth and macro economic variables, we find that large shareholder without knowing who the owners are do not effect the firm performance. However, when the family and institution become dominance in controlling the company, market reacts negatively. It might occur because market perceives negative effect of disgorging cash by family and institutional that cause lower distribution profit for other minority shareholder in the market. Our finding provides the signal for company which majority of shareholder need to provide more transparance report on flowing the cash flows of company. Additionally for the new investors who expect to have capital gain on the investment must take fully concern on this condition, because their value of investment could decrease and get loss if they invest in this type of companies.